Analysis Of The ‘Apam’ System On The Level Of Satisfaction Of Geriarti Patients Based On The ‘Eucs’ Method AT Rs Bunda Palembang - Restetty, Eueis; Prapanca, Yuli; Nugroho, Dedy; Agustin, Dinni (Journal of Ageing And Family, 2024)
In providing safe, quality, and affordable health services for everyone in the hospital, it is necessary to rely intensively on information. The development of information technology that needs to be developed at this time is a patient registration information system. An important indicator in the success of information system development is end user satisfaction. So user satisfaction plays a very important role in the success of an information system. Bunda Hospital Palembang is a Type C referral hospital, in the outpatient registration section, Bunda Hospital started using online registration in October 2024 by having 3 technology-based Independent Patient Platforms (APAM) systematically integrated with patient electronic medical records so that services become effective and efficient can reduce and break down long outpatient registration queues. The purpose of this study was to determine and explain the satisfaction of geriatric patients since the implementation of the outpatient independent patient platform (APAM) system at Bunda Hospital Palembang. The research method used was quantitative with a cross sectional research design, the research was conducted at Bunda Hospital Palembang in the span of January - February 2025. Sampling using the Slovin formula with a total of 100 respondents. From the results of the questionnaire it was found that all data were valid and reliable. Based on the F test, it can be seen that the P-value number is 0.000